O roli bionimów w procesie tworzenia ukraińskich oficjalnych nazw grzybów makroskopijnych - Jóźwikiewicz, Przemysław (Studia Ukrainica Posnaniensia, 2025)
The article discusses the issue of how bionyms function in the area of Ukrainian official names of macroscopic mushrooms. The analysis is embedded in onomastic and terminological research, which aimed to determine the extent of the occurrence of bionyms among the above mentioned names. The source materials were mainly academic papers on mycology, professional articles, guides and atlases of mushrooms, and Internet websites. It was found that phytonyms and anthroponyms predominate in the naming structures, while the names themselves most often function in the form of an attributive model with adjectives or adjectival participles. The exceptions here were eponyms, where the genetic model (N+NGen) predominates.